INVENTARISASI TUMBUHAN PAKU (PTERIDOPHYTA) DI KAWASAN KAMPUS IAIN PALANGKA RAYA SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN MATERI KLASIFIKASI TUMBUHAN - Dewi, Nor Apriyani (IAIN Palangka Raya, 2017)
The purpose of this research is to have an inventory on Fern-plants in the area of IAIN Palangka Raya as an alternative media to discuss or learn about the classification of plants for high school students. The method applied was qualitative research through survey activities to have an inventory on fern-plants. In collecting the data, the procedure was done by tracking the ferns growing area and collecting every kind of ferns species found in IAIN Palangka Raya. Identification of ferns species were using the key of determination. The data of the research were analyzed descriptively to get connected with the development of alternative learning media. The inventory result has beenÂ obtained eleven species of pteridophyta, one species of Blechnaceae family, two species of Pteridaceae, one species of Polypodiaceae, four species of Dryopteridaceae, two species of Polipodiacea and ome species of Woodsiaceae. Based on the nature of the ferns, eleven ferns are found. They consist of six types of terrestrial Pteridophyta, two types of Pteridophyta epiphytes and teresters, and three types of Pteridophyta epiphytes. The results of the research can be used as an alternative media for teaching and learning the topic of plant classification for high school students.